2020
DOI: 10.1111/jan.14441
|View full text |Cite
|
Sign up to set email alerts
|

Can a participatory organizational intervention improve social capital and organizational readiness to change? Cluster randomized controlled trial at five Danish hospitals

Abstract: Aim: This study investigates the effect of a participatory organizational intervention on social capital and organizational readiness for change. Design: Cluster randomized controlled trial. Methods: In 2016, 27 departments from five hospitals in Denmark were randomly allocated at the department level to 1 year of participatory intervention (14 clusters, 316 healthcare workers) or a control group (13 clusters, 309 healthcare workers). The participatory intervention consisted of 2 × 2 hr workshops, where manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 45 publications
2
13
0
Order By: Relevance
“…Top management refers to the mindset of top management in favour of the related technologies and the extent of funding for implementation [25]. Support for upper management is one of the most significant aspects of sustaining and supplementing the tools required for implementing emerging technologies.…”
Section: Top Management Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…Top management refers to the mindset of top management in favour of the related technologies and the extent of funding for implementation [25]. Support for upper management is one of the most significant aspects of sustaining and supplementing the tools required for implementing emerging technologies.…”
Section: Top Management Supportmentioning
confidence: 99%
“…Business readiness refers to the availability of company services required for technological implementation [25]. A company's preparation covers cloud computing platform infrastructure, finance, information technology and human resources.…”
Section: Organization Readinessmentioning
confidence: 99%
“…Meanwhile, nurses' workplace social capital can be classi ed into three types, bonding, bridging, and linking. Bonding and bridging in the context of social capital describe relationships established within and/or among groups at the same professional and power level and, therefore, is regarded as horizontal social capital; in contrast, linking social capital represents relationships across different strata of power and is considered vertical social capital [4,14,21]. The diagram of the constitution of this focal concept is depicted in Fig.…”
Section: The Focal Concept Of the Conceptual Modelmentioning
confidence: 99%
“…The spectrum of effect modi ers of nurses' workplace social capital is broad and not exclusive to communication. For example, visual management tools in nurses' daily work have been reported to positively modify nurses' workplace social capital [29]; research has supported the positive effects of the organizational intervention of participatory workshops on the topic of utilizing assistive devices in patient handling, or group-based physical exercise on nurses' workplace social capital [21,30]. Finally, urgency, e ciency, and immediacy of delivery of healthcare services can be viewed as a positive effect modi er on nurses' workplace social capital.…”
Section: Determinants Of Nurses' Workplace Social Capital and Their Rmentioning
confidence: 99%
“…They concluded that "it is more reasonable to interpret our finding as an indication that organizational changes which in the current health policy climate are often motivated by cutting costs and increasing control and efficiency may indeed create more work system performance obstacles" (11), adding that "participation in decisionmaking is an aspect of such engagement and should be encouraged and safeguarded by hospital leadership in change processes as well as in day-to-day operations" (11). There is literature that examines organizational change in hospitals in terms of change tactics and methods suggesting that those at lower levels should be given as much autonomy and flexibility as possible to implement change at their levels (12,13).…”
Section: Introductionmentioning
confidence: 99%